The expression patterns and putative function of nitrate transporter 2.5 in plants. (1st December 2020) - Liu, Ranran; Jia, Ting; Cui, Bing; Song, Jie
ABSTRACT: Nitrate transporter 2.5 (NRT2.5) was originally characterized as the transporter for nitrogen (N) limitation. In Arabidopsis, NRT2.5 is expressed mainly under extremely low NO3 − and N starvation conditions, and this must work in conjunction with NAR2.1. NRT2.5 is expressed both in the roots and leaves in Arabidopsis, poplars, tea trees and cassava. This is also expressed in the seeds of Arabidopsis and wheat. In wheat, NRT2.5 is expressed in the embryo and shell and plays a role in the accumulation of NO3 − in the seeds. In maize, this is also expressed in silk, cobs and tassel husk leaves. In rice, OsNRT2.5 (also known as OsNRT2.3a ) may help the species to remove NO3 − from the roots to shoots. In addition, NRT2.5 may interact with TGA3, MYC1, LBD37, LBD38, TaNAC2 and other transcription factors and participate in the transmission of NO3 − signals. The present review summarizes the functions of NRT2.5 in different plant species, which may help plant breeders and molecular biologists to improve crop yield. Abbreviations: NRT, Nitrate transporter; NUE, nitrogen use efficiency; PTR, peptide transporter; NPF, nitrate peptide transporter family; CLC, chloride channel; LAC1/SLAH, slow anion channel-associated 1 homolog 3; LATS, low-affinity transporter systems; HATS, high-affinity transport systems; NNP, nitrate-nitrite-porter; MFS, major facilitator superfamily.